Downbeat Nystagmus Induced by Sedation in Lasik - Miguel Paciuc-Beja; Gerardo Mendieta (Case Reports in Ophthalmological Medicine)
Nystagmus was elicited during lasik under sedation in two patients that were treated for depression. Nystagmus was not present before or after surgery. Nystagmus can be pharmacologically induced and can be a hazard to refractive surgery.